Svansbitning hos gris relaterat till individuell tillväxt och ras - Westin, Rebecka (SLU/Dept. of Animal Environment and Health (until 231231), 2003)
The purpose with this study was to find out if tailbiting pigs have a higher or lower daily weight gain than non-tailbiting pigs in the same pen before tailbitingbehaviour occur. The purpose was also to compare the occurrence of tailbiting between different breeds (Swedish Landrace, Yorkshire and Hampshire). Tailbiting among pigs has been a problem for pigfarmers a long time. Tailbiting means reduced animal welfare for the pig and economical loss for the farmer. The results of this study are based on statistical analyses. The data was collected from a database linked to a special breeding evaluation farm. Individual weight and daily weight gain was compared between the categories 'tailbiter', 'victim' and 'neutral pig'. The results show that tailbiters have a lower daily weight gain than other pigs before they start to tailbite. Five weeks after arrival at the farm, the difference in weight was significant. Disease, stress and feeding are some factors discussed. The results also show that Landrace pigs are more disposed to become tailbiters than Yorkshire and Hampshire pigs.